Uji Aktivitas Formulasi Mikrokapsul Ekstrak Etanol Daun Salam (Syzygium polyanthum) Sebagai Antidislipidemia Terhadap Tikus Putih - Stefanus Rio Pendamenta Tarigan; Razoki Razoki; Erida Novriani (Lembaga Pengembangan Kinerja Dosen, 2025)
Dyslipidemia is a lipid metabolism disorder characterized by elevated levels of total cholesterol, triglycerides, and low-density lipoprotein (LDL) accompanied by decreased levels of high-density lipoprotein (HDL). This condition is a major risk factor for atherosclerosis, coronary heart disease, and stroke. One plant with potential as an antidyslipidemic agent is bay leaves (Syzygium polyanthum). These leaves are known to contain active compounds such as flavonoids, saponins, tannins, alkaloids, and polyphenols that have antioxidant and hypolipidemic activities. The potential of natural compounds from medicinal plants to reduce blood cholesterol levels has gained significant attention in recent years. This study aims to evaluate the effectiveness of microencapsulated ethanol extract of bay leaves in reducing total cholesterol levels in white rats (Rattus norvegicus) induced by a high-cholesterol diet. The experimental study design employed was a laboratory-based true experimental method with a post-test control group design. A total of 25 male rats were used and divided into six groups: normal control, negative control (high cholesterol diet without therapy), positive control (simvastatin), and three groups treated with bay leaf extract microencapsulates at doses of 0.25%, 0.5%, and 0.75%. The treatment was given for 14 days, then total cholesterol levels were measured using an enzymatic method. The results showed that the group with a dose of 0.75% experienced the highest decrease in total cholesterol levels, namely -70 mg/dL, greater than the simvastatin group (-49 mg/dL). Statistical analysis using One Way ANOVA showed a significant difference compared to the negative control (p < 0.001). These findings indicate that the 0.75% dose of microencapsulated Syzygium polyanthum extract demonstrated an effect equal to or greater than simvastatin. Thus, it can be concluded that bay leaf ethanol extract microencapsulates are effective in reducing total cholesterol levels in hypercholesterolemic rats. This suggests that Syzygium polyanthum microencapsulation has the potential to be developed as an alternative phytotherapy for cholesterol reduction.